Pallidal gap junctions-triggers of synchrony in Parkinson's disease? - Schwab, Bettina C (Mov Disord, 2014)
Although increased synchrony of the neural activity in the basal ganglia may underlie the motor deficiencies exhibited in Parkinson's disease (PD), how this synchrony arises, propagates through the basal ganglia, and changes under dopamine replacement remains unknown. Gap junctions could play a major role in modifying this synchrony, because they show functional plasticity under the influence of dopamine and after neural injury. In this study, confocal imaging was used to detect connexin-36, the major neural gap junction protein, in postmortem tissues of PD patients and control subjects in the putamen, subthalamic nucleus (STN), and external and internal globus pallidus (GPe and GPi, respectively). Moreover, we quantified how gap junctions affect synchrony in an existing computational model of the basal ganglia. We detected connexin-36 in the human putamen, GPe, and GPi, but not in the STN. Furthermore, we found that the number of connexin-36 spots in PD tissues increased by 50% in the putamen, 43% in the GPe, and 109% in the GPi compared with controls. In the computational model, gap junctions in the GPe and GPi strongly influenced synchrony. The basal ganglia became especially susceptible to synchronize with input from the cortex when gap junctions were numerous and high in conductance. In conclusion, connexin-36 expression in the human GPe and GPi suggests that gap junctional coupling exists within these nuclei. In PD, neural injury and dopamine depletion could increase this coupling. Therefore, we propose that gap junctions act as a powerful modulator of synchrony in the basal ganglia.